POWER Learning:Strategies For Success In Collede And Life - Feldman,Robert S (New York McGrow-Hill, 2011)
Features the scientifically-based,yet simple and class-tested principles of the POWER (Prepare, Organize,Work,Evaluate,and Rethink)system that helps students gain a sense of mastery and Read more....
Keywords: College student orientation.:Study skills.:Life Skills